The Conversion of Jatropha Oil into Jet Fuel on NiMo/Al‐MCM‐41 Catalyst: Intrinsic Synergic Effects between Ni and Mo. Issue 5 (17th April 2019) - Du, Xiangze; Li, Dan; Xin, Hui; Zhou, Wenjun; Yang, Rui; Zhou, Keyao; Hu, Changwei
Abstract : Although there is much work focused on the conversion of biomass oil into a fuel on bimetallic Ni‐ and Mo‐based catalysts, the intrinsic synergic effects of Ni and Mo have not been revealed clearly. Herein, Mo/Al‐MCM‐41, Ni/Al‐MCM‐41, and NiMo/Al‐MCM‐41 catalysts are synthesized and used for the catalytic conversion of jatropha oil into jet fuel through a one‐step process. The molecular weight range (150–180 Da) of the jet fuel, obtained with a high yield of 63 wt% over 10% NiMo/Al‐MCM‐41 catalyst, is almost the same as that of the commercial aviation fuel of China. A bimetallic catalyst shows not only an excellent activity but also a high carbon‐resistance nature compared with a monometallic catalyst. Characterizations using X‐ray diffraction, Raman spectroscopy, H2 ‐temperature‐programmed reduction, high‐angle annular dark‐field detector high‐resolution transmission electron microscopy (HADDF‐TEM)‐mapping, and in situ X‐ray photoelectron spectroscopy reveal that the formation of elliptical particles containing both Ni and Mo species and of appropriate acid sites with a proper density on the NiMo/Al‐MCM‐41 catalyst would result in a high yield of the jet fuel. Moreover, the electron transfer from Ni to Mo by a surface synergetic oxygen vacancy of Ni–Mo on the NiMo/Al‐MCM‐41 catalyst might be responsible for the excellent anti‐coke ability. Abstract : The catalytic conversion of jatropha oil into jet fuel is performed by the hydrodeoxygenation on the NiMo/Al‐MCM‐41 catalyst. Intrinsic synergic effects between Ni and Mo by a surface synergetic oxygen vacancy of Ni‐□‐Mo might be responsible for the excellent catalytic performance and high carbon resistance.